2012
DOI: 10.1371/journal.pone.0043021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Dietary Fatty Acid Restriction in Patients with Phenylketonuria

Abstract: BackgroundPatients with phenylketonuria (PKU) have to follow a lifelong phenylalanine restricted diet. This type of diet markedly reduces the intake of saturated and unsaturated fatty acids especially long chain polyunsaturated fatty acids (LC-PUFA). Long-chain saturated fatty acids are substrates of mitochondrial fatty acid oxidation for acetyl-CoA production. LC-PUFA are discussed to affect inflammatory and haemostaseological processes in health and disease. The influence of the long term PKU diet on fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Second, phenylketonuria patients generally consume a vegetarian diet, especially well-controlled patients who strictly comply with this low-cholesterol diet. 8,22 Our results support this hypothesis. Numerous studies have shown that people consuming vegetarian and also vegan diet had lower high-density lipoprotein cholesterol levels compared with omnivorous healthy people.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Second, phenylketonuria patients generally consume a vegetarian diet, especially well-controlled patients who strictly comply with this low-cholesterol diet. 8,22 Our results support this hypothesis. Numerous studies have shown that people consuming vegetarian and also vegan diet had lower high-density lipoprotein cholesterol levels compared with omnivorous healthy people.…”
Section: Discussionsupporting
confidence: 86%
“…There are few studies that have investigated the known risk factors of atherosclerosis, such as blood lipids, homocysteine, and mean platelet volume in phenylketonuria patients, in the literature. 3,[6][7][8][9][14][15][16][17][18][19][20][21][22] In most of these previous studies, these factors were evaluated independently, and only one of them included mean platelet volume levels. 22 The primary aim of the present study was to investigate the serum atherogenic markers in adolescent phenylketonuria patients and compare these parameters with healthy peers.…”
mentioning
confidence: 99%
“…Our data indicate that better compliance with the diet may be associated with a reduced prevalence of overweight and obesity. PKU patients have a low-protein diet which is comparable to a vegetarian diet [34], leading to less fatty acid intake [35] and more contribution of carbohydrates in order to complete their energetic needs [36]. Our data, regarding nutritional intake seems to be in accordance with this statement, showing relatively low fat intake but huge contribution from carbohydrates compared with Portuguese non-PKU population [37].…”
Section: Discussionsupporting
confidence: 82%
“…DHA and EPA are known to have cardio-protective effects [43] and deficiencies may lead to CNS disease or affect the immune system [42]. Normal as well as reduced plasma and erythrocyte FA levels have been reported in patients with PKU [44,45,46,47,48,49]. It is, however, not clear what these deficiencies mean and if they have a clinical impact on the patients.…”
Section: Discussionmentioning
confidence: 99%